Antifungal effect of chemical agents in yeasts with pathogenic potential isolated from veterinary hospital environment - Mattei, Antonella Souza (2013)
Hospital environments can have pathogens and opportunistic pathogens, important for immunocompromising individuals. The process of cleaning and disinfection constitutes an important measure for the control of these diseases. This study evaluated the sensitivity of yeasts isolated from surfaces of nosocomial veterinary environment to four disinfectants/antiseptics used in the routine of disinfection. The test of broth microdilution was carried in 24 isolates of yeasts against 4% sodium hypochlorite, 2% benzalkonium chloride, 6.6% chlorexidine-cetrimide and 3% chloro-phenol derivate. Chlorexidine-cetrimide, benzalkonium chloride and chloro-phenol derivate were efficient in all isolates with minimal inhibitory concentration and minimal fungicide concentration lower than the concentration recommended by manufacturer. By other hand, fungicide action of the sodium hypochlorite in the concentration recommended by the manufacturer was verified in 79.1% of the isolated tested, with the lower performance of than the others evaluated disinfectants.